Gaya Belajar Dalam Perspektif Motivasi Dan Kreativitas Pada Mahasiswa Pendidikan Akuntansi Angkatan 2015 Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta - PUJI HASTUTI, DWI, Dr. Sabar Narimo, MM,M.Pd (2016)
The purposes of the study are: 1) To determine the effect of motivation on learning styles of Students Force 2015 of Accounting Teaching and Education Faculty UMS; 2) To determine the effect of creativity on learning styles of Students Force 2015 of Accounting Teaching and Education Faculty UMS; and 3) To determine both the influence between motivation and creativity of Students Force 2015 of Accounting Teaching and Education Faculty UMS. The type of this research is a quantitative associative research, by taking at Teaching and Education Faculty, University of Muhammadiyah Surakarta. The population in this study is 248 students and sample is 146 students. The technique of collecting data uses multiple linear regression analysis; t and F test, and also the determination coefficient, the relative and effective calculation. The results of this study show that: 1) There is an effect between motivation to the learning style of Students Force 2015 of Accounting Teaching and Education Faculty UMS. It can be seen from the results of the t test analysis shows that tcount> ttable, is 2.249 ˃ 1,977 significance ˂ 0.005 ie 0.026, the effective calculation of 10.8%; 2) There is effect between creativity to the learning styles of Students Force 2015 of Accounting Teaching and Education Faculty UMS. It can be seen from the results of the t test analysis shows that tcount> ttable, is 3.534 ˃ 2.007 significance ˂ 0.005 ie 0.001, the effective calculation of 27.4%; and 3) Both the motivation and creativity effect to the learning styles of Students Force 2015 of Accounting Teaching and Education Faculty UMS. It can be seen from the results of F test analysis shows that Fcount> Ftable, is 12.227> 3.059 and the significance <0.05 is 0.000. The result of coefficient of 0.382 which indicates that the effect of motivation and creativity to the learning styles of 38.2%, while 61.8% is influenced by other variables are not studied, such as parental education, the environment, technology sophisticated increasingly and other variables are likely to have effect towards learning style.